Resistance to Acetolactate Synthase-Inhibiting Herbicides in Annual Ryegrass (Lolium rigidum) Involves at Least Two Mechanisms - Christopher, John T. (1992)
WLR1, a biotype of Lolium rigidum Gaud. that had been treated with the sulfonylurea herbicide chlorsulfuron in 7 consecutive years, was found to be resistant to both the wheat-selective and the nonselective sulfonylurea and imidazolinone herbicides. Biotype SLR31, which became cross-resistant to chlorsulfuron following treatment with the aryloxyphenoxypropionate herbicide diclofop-methyl, was resistant to the wheat-selective, but not the nonselective, sulfonylurea and imidazolinone herbicides. The concentrations of herbicide required to reduce in vitro acetolactate synthase (ALs) activity 50% with respect to control assays minus herbicide for biotype WLR1 was greater than those for susceptible biotype VLR1 by a factor of >30, >30, 7,4, and 2 for the herbicides chlorsulfuron, sulfometuron-methyl, imazapyr, imazathapyr, and imazamethabenz, respectively. ALS activity from biotype SLR31 responded in a similar manner to that of the susceptible biotype VLR1. The resistant biotypes metabolized chlorsulfuron more rapidly than the susceptible biotype. Metabolism of 50% of [phenyl-U-(14)C]chlorsulfuron in the culms of two-leaf seedlings required 3.7 h in biotype SLR31, 5.1 h in biotype WLR1, and 7.1 h in biotype VLR1. In all biotypes the metabolism of chlorsulfuron in the culms was more rapid than that in the leaf lamina. Resistance to ALS inhibitors in L. rigidum may involve at least two mechanisms, increased metabolism of the herbicide and/or a herbicide-insensitive ALS.